AB0566 18f-fdg-pet-positive temporal artery in giant cell arteritis: a possible correlation with histopathological findings. (15th June 2017) - Kono, H; Okada, Y; Asako, K; Kikuchi, H; Oguchi, Y; Honda, Z-I; Takeuchi, A; Tokairin, T; Saito, K
Abstract : Background: Giant cell arteritis (GCA) a form of vasculitis in persons older than 50 years, in which cranial and systemic large vessels can be involved. 18 F-fluorodeoxyglucose positron emission tomography - computed tomography ( 18 F-FDG-PET-CT) is increasingly used to diagnose inflammation of the large arteries in GCA. But it is very rare to observe an inflammation of temporal arteries of GCA using 18 F-FDG-PET. Objectives: To understand the mechanism and frequency of the positive temporal artery of GCA in 18 F-FDG-PET. Methods: This was a retrospective chart review of 3 patients with giant cell arteritis who underwent all of 18 F-FDG-PET, MRI, CT angiogram, ultrasound and histopathologic evaluation of temporal arteries. To investigate the cases of FDG-PET positive temporal arteries in GCA, a systematic literature review was done in Pubmed using 18 F-FDG-PET AND ("temporal arteritis" OR "giant cell arteritis"). Results: A case report: An 85-year-old male presented with muscle weakness. Three years before admission, he experienced pain in his neck and both extremities. Rheumatoid arthritis was diagnosed at another hospital, and the patient was treated with methotrexate and prednisolone, which resolved his symptoms. The medication was discontinued after 2 years. Two months before admission he began coughing due to interstitial pneumonitis, and later developed muscle weakness and difficulty walking. On admission a physical examination revealed swelling of the bilateral temporal arteries. A blood test showed accelerated ESR at 54mm/h and a CRP of 4.6 mg/dL. Ultrasound showed an increased diameter, hypoechoic wall thickening (halo), stenosis, and calcification of the arterial wall of the temporal artery. A contrast CT showed wall thickening in the affected segments, calcification, stenosis and enhancement of the soft tissue around the temporal artery. An 18 F-FDG-PET scan indicated increased uptake of 18 F-FDG at the temporal arteries whereas no uptake was found in the other arteries including the aorta and carotid arteries. A biopsy of the temporal artery revealed necrotizing vasculitis with a few giant cells and the formation of a microscopic neutrophilic abscess. When compared with 2 other cases of temporal arteritis with a negative 18 F-FDG uptake, the severity of inflammation and the number of giant cells in the present case were not remarkably high. A systematic literature review identified 4 cases of 18 F-FDG-PET positive temporal arteries in 454 cases of GCA of 82 papers. Of note, large arteries were positive for 18 F-FDG-PET in 253 cases of GCA in the same series. Conclusions: The hierarchy for FDG uptake by resting inflammatory cells is neutrophil > macrophage = lymphocyte in vitro, indicating that the sites where neutrophils dominate are more likely to be visualized by 18 F-FDG PET in vivo. In addition to the known usefulness of 18 F-FDG-PET in visualizing inflammation in large vessels, the increased uptake of 18 F-FDG to the temporal artery may help to identify the neutrophilic inflammation. Disclosure of Interest: None declared